Radiation Lobectomy: An Overview of Concept and Applications, Technical Considerations, Outcomes - Entezari, Pouya; Gabr, Ahmed; Kennedy, Kristie; Salem, Riad; Lewandowski, Robert J. (Seminars in Interventional Radiology, 2021)
Surgical resection has long been considered curative for patients with early-stage hepatocellular carcinoma (HCC). However, inadequate future liver remnant (FLR) renders many patients not amenable to surgery. Recently, lobar administration of yttrium-90 (Y90) radioembolization has been utilized to induce FLR hypertrophy while providing disease control, eventually facilitating resection in patients with hepatic malignancy. This has been termed “radiation lobectomy (RL).” The concept is evolving, with modified approaches combining RL and high-dose curative-intent radioembolization (radiation segmentectomy) to achieve tumor ablation. This article provides an overview of the concept and applications of RL, including technical considerations and outcomes in patients with hepatic malignancies.
Keywords: radiation lobectomy; radioembolization; future liver remnant; hepatocellular carcinoma; interventional radiology